Peran Komite Sekolah dalam Meningkatkan Kualitas Sarana dan Prasarana di MTs Mambaul Ulum Musi Banyuasin - Ibrahim; Ari Muhtadin Kurniawan; Ahmad Zainuri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
This research is entitled “The Role of School Committees in Improving the Quality of Facilities and Infrastructure at MTs Mambaul Ulum Musi Banyuasin